Design of Gleason High-ratio Hypoid Gear with Parallel Tooth Depth - Wang Zhiyong; Li Chaoyue; Huang Denghong (Jixie chuandong)
The keys of design of high-ratio hypoid gears are determinations of gear and pinion pitch cone and calculations of geometric parameters. The research of the design of Gleason high-ratio hypoid gears with parallel tooth depth is carried out. The geometric constraints of spiral angle,pinion offset,face width and addendum factors are given out. The calculation method of geometric parameters are established. A pair of high-ratio hypoid gear which has the gear ratio of 1: 120 is designed. Through the actual machining,the correctness of the design method of high-ratio hypoid gears with parallel tooth depth is verified.